Маркетинговые исследования влияния внешних факторов на рынок молока - Гриднева, Д. Ю.; Кулиш, Татьяна Владимировна; Куліш, Тетяна Володимирівна; Kulish, Tetiana (ИжГТУ имени М.Т. Калашникова, 2015)
RU: В статье раскрыты основные проблемы развития рынка молока. Выявлено влияние внеш-них факторов на рынок молока, а также определены альтернативные направления развития рынка. EN: The article reveals the basic problems of development of the milk market. The influence of exter-nal factors on the milk market was identified and alternative directions of development of the market were defined.
Marketing research of the influence of external factors on the milk market
Keywords: маркетинговые исследования; внешние факторы; рынок молока; политико-правовые факторы; экономические факторы; демографические факторы; социально-культурные факторы; природные факторы; научно-технические факторы; marketing research; external factors; milk market; scientific and technical factors; socio-cultural factors; natural factors; demographic factors